Characterization of electrical properties of organic-rich shales at nano/micro scales. (September 2017) - Wang, Wenxiu; Li, Jin; Fan, Meng; Abedi, Sara
Abstract: A new experimental protocol is explored to characterize electrical properties of hydrocarbon-bearing mudrocks at nano/micro scales. Two current flow regimes of peak force - tunneling atomic force microscopy (PF-TUNA) have been used: (1) the vertical out-of-plane current regime with hundred micrometer diameter top electrodes obtains homogenized conductivity quantitatively, (2) the horizontal in-plane current regime was shown powerful to visualize the conductive paths (related to connectivity and tortuosity) for heterogeneous and anisotropic shales. Results show that the approach works well with one to two layers of adsorbed water (25–55% relative humidity) under low frequency (0.5–20 Hz) for shale rocks. Current maps with sub-nanometer resolution emphasize the dominant role of hydrated ions associated with the hydrophilic clay minerals in driving the dielectric response of shales, while conductivity of pyrite and kerogen cannot be neglected for mature organic-rich shale conductive network. The acquired I-V curves at microscale provide a reliable mean to evaluate homogenized conductivity of such multiscale multi-component heterogeneous material under controlled environmental conditions. The procedure discussed herein serves as a complement for fine grained rocks and minerals of ionic-electronic hybrid conductive mechanism under partially water saturation. These results can be used to develop accurate electrical models, specifically for shale rocks with heterogeneous and sophisticated microstructure. The methodology can be also extended to other micro- or meso-porous geomaterials such as cementitious and bituminous nanoporous media.